Wuda Granule Alleviates DSS-Induced Colitis in Mice by Inhibiting Inflammation, Protecting Intestinal Barrier and Reducing Oxidative Stress Through Nrf2/Keap1/HO-1 Pathway - Wang T; Ou Y; Xiong W; Luo L; Xu Y; Chen G; Peng Y; Chen Y; Zeng H; Yu Y; Tang H; Yao H; et al. (Journal of Inflammation Research, 2025)
Tao Wang,1,2 Yanghui Ou,3 Wenjun Xiong,1,2 Lijie Luo,1,2 Yihua Xu,4 Guojian Chen,1,2 Yaohui Peng,1,2 Yan Chen,1,2 Haiping Zeng,1,2 Yang Yu,1,2 Haipeng Tang,1,2 Hongliang Yao,3 Wei Wang1,2 1Department of Gastrointestinal Surgery, The First Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, 510405, People’s Republic of China; 2Guangdong Clinical Research Institute of Chinese Medicine, Guangzhou, Guangdong, 510405, People’s Republic of China; 3Guangdong Key Laboratory of Animal Conservation and Resource Utilization, Institute of Zoology, Guangdong Academy of Sciences, Guangzhou, Guangdong, 510260, People’s Republic of China; 4Southern Medical University Hospital of Integrated Traditional Chinese and Western Medicine, Guangzhou, Guangdong, 510315, People’s Republic of ChinaCorrespondence: Wei Wang, Email wangwei16400@163.com Hongliang Yao, Email yaohl@giz.gd.cnBackground: Colitis, a inflammatory disorder of the colon, causes significant morbidity and declines quality of life. Despite treatment advancements, effective therapies remain limited. Wuda Granules (WDG), a traditional medicine formula, is clinically used for intestinal obstruction and gastrointestinal recovery through its anti-inflammatory effects.Methods: Network pharmacology and molecular docking were employed to identify the active compounds, key targets, and associated signaling pathways of WDG against Colitis. A mouse model of DSS-induced colitis was established to evaluate the therapeutic potential of WDG. Colitis-related symptoms, including weight loss, DAI score, spleen index, and colon length, were measured. Histopathological changes were analyzed using H&E staining. To assess intestinal barrier integrity, goblet cell abundance was determined by AB-PAS staining, and the expression of related proteins was analyzed by IHC. Inflammatory and oxidative stress markers were measured by ELISA, biochemical assays, and Western blotting.Results: Network pharmacology analysis identified the core therapeutic targets of WDG against UC is IL-6, TP53, AKT1, IL-1β, and TNF. WDG treatment significantly improved colitis-related symptoms, as evidenced by reduced weight loss, DAI score, and spleen index, as well as increased colon length. Histological analysis revealed preserved colon structure and reduced inflammatory infiltration. WDG suppressed the expression of pro-inflammatory mediators (IL-6, IL-1β, TNF-α, MPO) and enhanced the levels of anti-inflammatory cytokines (IL-10 and IL-22). In addition, WDG alleviated lung inflammation and inhibited M1 macrophage polarization. Intestinal barrier integrity was improved by increasing goblet cell numbers and upregulating the expression of MUC2, ZO-1, Occludin, Claudin-1. Antioxidant activity was enhanced, indicated by elevated SOD and CAT levels and decreased MDA content. Mechanistically, Western blot analysis showed that WDG activated the Nrf2/Keap1/HO-1 signaling pathway. Molecular docking further revealed one potential active compound, 6,7-Dimethoxy-2-(2-phenylethyl) chromone, which exhibited strong binding affinity with Nrf2/Keap1 complex.Conclusion: WDG alleviates DSS-induced colitis by inhibiting inflammation, enhancing intestinal barrier integrity, and reducing oxidative stress through activation of the Nrf2/Keap1/HO-1 pathway.Keywords: wuda granule, colitis, anti-inflammatory, antioxidant, intestinal barrier protection